Emma sugar and spice and everything nice - Simon, Coco (Simon, Coco. Cupcake diaries ;, 2013)
Emma's younger brother Jake has tonsillitis and makes life difficult for Emma, while the Cupcake Club girls are spoiling him with cupcakes and little gifts.